The interpretation and visual attention of hearing impaired children when watching a subtitled cartoon - Cristina Cambra; Aurora Leal; Núria Silvestre (JoSTrans: The Journal of Specialised Translation)
The article analyses how hearing impaired children interpret a subtitled cartoon, taking into account their visual attention to both sources of information (the images and the subtitles), and the auditory information from the oral language. The sample was made up of eleven children, aged seven to eleven years old (second to fifth grade of elementary school), who attend ordinary mainstream schools in Barcelona in the oral mode. A narrative cartoon with subtitles in Catalan was used in the study. The eye movement of the subjects was also analysed using an eye-tracker as the subjects watched the audiovisual story. After seeing it, they were asked to orally retell the cartoon story. The results reveal the importance of having time to view the images to interpret the story well. The eye-tracker shows that the hearing impaired children who participated in the study maintained attention on the frames with subtitles, with the exception of the participants in second grade with lower reading skills who did not pay attention to the subtitles towards the end of the cartoon when the conflict of the story was resolved.